(untitled) (Journal of Forest and Livelihood, 2018)
This paper draws lessons from the development of Forest Reference Level (FRL) or Forest Emission Reference Level (FREL) in three selected countries in the Hindukush Himalayan (HKH) countries. Using a detailed textual analysis of the relevant documents of India, Myanmar and Nepal, the paper compares and contrasts the processes and contents of the FRLs of these countries. Based on literature on FRL/FREL, the United Nations Framework Convention on Climate Change (UNFCCC) guideline in particular, the paper identifies seven key criteria for comparing the documents, and then analyses major experiences and insights around those key criteria. It is learnt that both the processes and the contents of the FRL/FREL are diverse even within these three countries which can be attributed to the country contexts and capacities. Key variables reflecting country contexts influencing REDD+ (Reducing Emissions from Deforestation and Forest Degradation and the role of conservation, sustainable management of forests and enhancement of forest carbon stocks in developing countries), FRL/FREL are the socio-political contexts, forest-people relations, forest types and forest governance, and tenure arrangements. In addition, a country’s capacity in mobilising its own resources to conduct national forest monitoring and implementing REDD+ are reflected in their levels of comprehensiveness and precision of assessments and targets. The paper argues that, FRL/FREL documents are the negotiated outcomes of universal framework provided by the UNFCCC and that of national contexts and capacities. Therefore, a right balance of these two aspects will increase the likelihoods of effective and accurate measurement of REDD+ outcomes, in terms of carbon benefits particularly, in the context of low prospects of international funding for climate actions in the long run.